2021
DOI: 10.17016/2380-7172.2893
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Financial Stability

Abstract: This Note describes how risks arising from climate change may affect financial stability. We describe how climate-change related risks may emerge either as shocks to the financial system or as financial system vulnerabilities that could amplify the effects of these or other shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…Again, column 1 shows a naïve regression that excludes the set of fixed effects. The result shows a negative correla-tion between SLR risk exposure and leverage, suggesting that transactions of exposed properties on average are less likely to be financed with debt, consistent with existing conventional views (e.g., Litterman et al 2020;Brunetti et al 2021).…”
Section: Extensive Margin: Leverage Probabilitysupporting
confidence: 84%
See 2 more Smart Citations
“…Again, column 1 shows a naïve regression that excludes the set of fixed effects. The result shows a negative correla-tion between SLR risk exposure and leverage, suggesting that transactions of exposed properties on average are less likely to be financed with debt, consistent with existing conventional views (e.g., Litterman et al 2020;Brunetti et al 2021).…”
Section: Extensive Margin: Leverage Probabilitysupporting
confidence: 84%
“…These complications compound when there is belief disagreement across economic agents about future risks (Geanakoplos 2010;Simsek 2013), and belief disagreement is especially pronounced for climate change (Howe et al 2015;Ballew et al 2019). A hypothesis common in policy discussions is that those who are less concerned about climate risks (the "optimists") are more likely to make leveraged investment on assets exposed to climate risks -such as coastal real estate properties -relative to those who are more concerned about climate risks (the "pessimists") (e.g., Litterman et al 2020;Brunetti et al 2021). In fact, this hypothesis is consistent with the benchmark prediction in standard models of leveraged investments under belief disagreement (e.g., Geanakoplos 2010;Simsek 2013;Fostel and Geanakoplos 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The US lags its international counterparts in confronting climate-driven financial risks, although the regulatory landscape as it relates to these risks is rapidly evolving [ 9 , 170 – 173 ]. The FRB has acknowledged climate change as a potential threat to the financial system in the past [ 174 , 175 ], and more recently has connected climate change to its microprudential and macroprudential mandates in official publications [ 176 – 178 ], joined some 100 other central banks as members of the NGFS [ 179 ], formed working groups on supervisory and financial stability climate risk issues [ 180 ], and signaled its intention to conduct a pilot scenario analysis exercise for climate risk [ 180 – 137 ]. 5 This section considers whether and how climate-related systemic risk could be incorporated into the FRB’s stress testing regime, given the FRB’s financial stability regulatory authority and the design of existing stress tests.…”
Section: Climate Stress Testing Practicesmentioning
confidence: 99%
“…This, in turn, broadens the concern of financial authorities about the realisation of climate-related financial risks (Carney, 2015;Gros et al, 2016;Hilaire and Bertram, 2019;UNEP, 2020;Dunz and Power, 2021). Indeed, climate change is expected to negatively affect economic performance and financial stability (BIS, 2021;Hilaire and Bertram, 2019;Clerc et al, 2021;Brunetti et al, 2021). Financial supervisors' concern is supported by research results (Battiston et al, 2021a), which showed that investors are largely exposed to economic activities that could face losses induced by climate physical and transition risks (see e.g.…”
Section: Introductionmentioning
confidence: 99%